Red Sea War : How The Houthi Onslaught Affected the Security of the State - Estika, Febrina; Almubaroq, Hikmat Zakky; Sumarno, Ari Pitoyo (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigates the implications of Houthi attacks in the Red Sea on global maritime security and international trade. Utilizing qualitative research with literature review methodology, it explores the geopolitical and economic impacts of these disruptions, particularly in the Bab el-Mandeb Strait and surrounding regions. The findings highlight a dramatic shift in shipping routes as vessels divert from the Red Sea to the Cape of Good Hope, increasing transit times and costs. The attacks also exacerbate tensions in the Middle East, impacting regional stability and global trade dynamics, especially in energy supply. The study underscores the necessity of enhancing maritime security, diversifying trade routes, and intensifying international diplomatic efforts to mitigate these challenges.